2018
DOI: 10.1002/mp.13163
|View full text |Cite
|
Sign up to set email alerts
|

Use of a constrained hierarchical optimization dataset enhances knowledge‐based planning as a quality assurance tool for prostate bed irradiation

Abstract: Populating a KBP model with CHO data resulted in a high quality model. Since CHO plans can be generated automatically offline in a process that necessitates little to no user interaction, a CHO-KBP model can quickly adapt to changes in plan evaluation criteria or planning techniques without the need to wait to accrue sufficient numbers of clinical TEO plans. This may facilitate the use of KBP approaches for initial or ongoing quality assurance procedures and plan quality audits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Another comparison between RP models based on different initial plans has been recently published. In their work, Lin et al [36] compared a model generated from clinical trial-and-error based plans on prostate, with a model generated for the same patients, whose plans were optimized according to a constrained hierarchical optimization procedure, a very complex and time consuming process able to produce Pareto optimal plans. They concluded that the RP model populated with this second group of plans improved significantly the model quality, in terms of R 2 and DVH estimation bound width; the final clinical plan quality, however, was not significantly improved using the RP generated by this second group of plans, proving that the model quality does not necessarily translate into clinical plan quality.…”
Section: Discussionmentioning
confidence: 99%
“…Another comparison between RP models based on different initial plans has been recently published. In their work, Lin et al [36] compared a model generated from clinical trial-and-error based plans on prostate, with a model generated for the same patients, whose plans were optimized according to a constrained hierarchical optimization procedure, a very complex and time consuming process able to produce Pareto optimal plans. They concluded that the RP model populated with this second group of plans improved significantly the model quality, in terms of R 2 and DVH estimation bound width; the final clinical plan quality, however, was not significantly improved using the RP generated by this second group of plans, proving that the model quality does not necessarily translate into clinical plan quality.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al. 22 demonstrated that building KBP models with constrained hierarchical optimization plan data could result in a high-quality KBP model to be used to quickly adapt KBP to changes in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Once the model is built, however, KBP can quickly produce new plans by leveraging the predicted achievable plan for the new patient. Lin et al 22 demonstrated that building KBP models with constrained hierarchical optimization plan data could result in a high-quality KBP model to be used to quickly adapt KBP to changes in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Such parameters can be, e.g., beam settings, DVHs for target volumes and OARs, or full 3-D dose distributions. DVH prediction has been widely studied in recent years for most disease sites, e.g., head and neck [214], [226], [258], [272], [274], [281], prostate [210], [238], [251], [255], [264], [266]- [268], [270], [276], [281], upper GI [259], [265], [273], [280], lower GI [229], [254], [269], [277], [278], and breast [259], [262], [275]. A commercial software for DVH prediction is Varian RapidPlan.…”
Section: A Classical Auto-planning Strategiesmentioning
confidence: 99%